Competitive Anxiety, and Guilt and Shame Proneness From Perspective Type D and Non-type D Football Players - Kaplánová, Adriana (Frontiers in Psychology, 2021)
The precompetitive, competitive, and postcompetitive mental states of athletes are currently not sufficiently researched. Long-term exposure to stressors contributes to the formation of mental blocks and leads to various health problems. One of the factors that can explain the variability of athletes' reactions to stress is their personality. This study is the first to examine competitive anxiety, and guilt and shame proneness in the context of the reaction of football players to distress in sports. The study consists of 112 male football players aged 16–24 (21.00 ± 1.90) who were divided into type D and non-type D football players according to scoring on the Denollet Scale (DS14). Football players also filled out the Sport Anxiety Scale (SAS-2) and the Guilt and Shame Proneness Scale (GASP). The taxonomic approach was conducted to test and to examine differences in stressor intensity as a function of type D personality. A correlation, multivariate analysis of variance, and regression analysis were performed in the study. We found that type D football players were more afraid of failures in sports (worry), felt more often autonomous excitement concentrated in the stomach and muscles (somatic anxiety), and showed more frequent concentration disruption than did non-type D football players. We also found that although type D football players were more likely to rate their behavior as negative and inappropriate, they showed a much greater effort to correct it than did non-type D football players. Negative affectivity and social inhibition of type D football players were positively correlated with competitive anxiety. In addition, we noted lower levels of somatic anxiety and lower concentration disruption for football players who used escape strategies to manage stress. The shame proneness subscale monitoring negative self-evaluation was also closely related to the concentration disruption of football players. We found that the examination of athletes by type D personality is necessary due to the fact that negative affectivity and social inhibition are significant predictors of competitive anxiety of football players, which explains their worries at 24.0%, somatic anxiety at 8.2%, and concentration disruption at 10.6%.